2013
DOI: 10.5830/cvja-2013-023
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular haemodynamics in pre-eclampsia using brain naturetic peptide and tissue Doppler studies : cardiovascular topics

Abstract: AimTo determine early haemodynamic changes in pre-eclampsia (PE) using tissue Doppler echocardiography and brain natriuretic peptide (BNP), and to relate these changes to obstetric outcomes.MethodsConsenting primigravidae patients in the third trimester of pregnancy were included in the study, which was carried out in a large regional hospital in Durban, South Africa; 115 primigravidae (52 pre-eclamptics and 63 normotensive pregnant patients) attending the maternity unit including the antenatal clinics at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
0
12
1
2
Order By: Relevance
“…[9] However, there are conflicting studies of natriuretic peptide concentrations in postpartum studies with some reporting elevated NT-pro-BNP concentrations in women with previous pre-eclampsia at three to six months postpartum compared to women with non-complicated pregnancies [25] and others reporting no difference in BNP concentrations between women with previous pre-eclampsia and healthy controls at one to four weeks postpartum. [26,27] Postpartum comparison of BNP concentrations between women with pre-eclampsia and pre-existing chronic hypertension has not previously been reported, and no differences were identified in this study. The absence of any association between BNP concentration and future CVD risk suggests that this marker is unlikely to have any useful predictive value in clinical practice.…”
Section: Discussionmentioning
confidence: 57%
“…[9] However, there are conflicting studies of natriuretic peptide concentrations in postpartum studies with some reporting elevated NT-pro-BNP concentrations in women with previous pre-eclampsia at three to six months postpartum compared to women with non-complicated pregnancies [25] and others reporting no difference in BNP concentrations between women with previous pre-eclampsia and healthy controls at one to four weeks postpartum. [26,27] Postpartum comparison of BNP concentrations between women with pre-eclampsia and pre-existing chronic hypertension has not previously been reported, and no differences were identified in this study. The absence of any association between BNP concentration and future CVD risk suggests that this marker is unlikely to have any useful predictive value in clinical practice.…”
Section: Discussionmentioning
confidence: 57%
“…Seven studies reported on BNP levels,78, 79, 80, 81, 82, 83, 84 of which three were applicable for a meta‐analysis ( Figure 5). 78, 79, 80 …”
Section: Resultsmentioning
confidence: 99%
“…One study reported on FABP4 levels in pre-eclampsia compared with controls and found statistically higher FABP4 levels in pre-eclampsia vs. non-hypertensive pregnancy. 77 Myocardial failure markers in pre-eclampsia Brain natriuretic peptide and N-terminal pro-BNP Seven studies reported on BNP levels, [78][79][80][81][82][83][84] of which three were applicable for a meta-analysis ( Figure 5). [78][79][80] In all seven studies and in meta-analysis, BNP levels were significantly higher in pre-eclampsia than in controls.…”
Section: Insulin Plasma Glucose and Fatty Acid-binding Proteinmentioning
confidence: 99%
“…This increase has been attributed to a rise in the tissue Doppler early filling wave (E′) and has been suggested to reflect rising cardiac filling pressures in preeclampsia. 38 However, it has been shown that preeclamptic women are preload responsive, ie, they increase their CO in response to volume load. 33,39 Although in clinical practice, pulmonary artery occlusion pressure is considered to reflect preload (pressure is easier to assess than the flow and volume), preload is related to filling blood volume rather than the filling pressure, and left atrial and ventricular pressures are a function of blood inflow and chamber compliance.…”
Section: Discussionmentioning
confidence: 99%